Installation capacity assessment of damaged deepwater pipelines - Ramasamy, R. (EDP Sciences, 2014)
The worldwide exploration and development of subsea and deepwater reservoirs has laid down some new and old engineering challenges to the offshore pipeline industry. This requires large D/t pipelines to be installed at water depths in the vicinity of up to 2700m. The deepwater collapse and buckle propagation event is almost unavoidable as the pipe wall thickness cannot be always determined from the codes and standards due to the limit state criteria. These codes also do not consider any fabrication imperfections and sustained damages emanating from transportation and handling. The objective of this paper is to present the Finite Element Analysis (FEA) of dented pipes with D/t ratio more than 45, which is outside the applicability of current design codes, and to investigate the effects on installation capacity of these various damage sizes in terms of collapse and buckle propagation. Â© 2014 Owned by the authors, published by EDP Sciences.